2017
DOI: 10.3892/ol.2017.6475
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, biological evaluation and mechanism studies of matrine derivatives as anticancer agents

Abstract: Abstract.A total of five matrine derivatives were synthesized and evaluated for their anti-proliferation activity using a panel of four human cancer cell lines, including A549 lung, BT20 breast, MCF-7 breast and U2OS osteosarcoma cells. The YF3-5, YF3-7 and YF3-9, three novel compounds, demonstrated increased anti-proliferation activity compared with matrine, of which YF3-5 revealed the strongest anti-proliferation activity with a half-maximal inhibitory concentration value of 15.49-16.67 µM against the four h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…106 In addition, three novel compounds (YF3-5, YF3-7 and YF3-9) all demonstrated anti-proliferation activity, of which YF3-5 showed the strongest anti-proliferation properties against the four human cancer cell lines (BT20 breast, MCF-7 breast, A549 lung and U2OS osteosarcoma cells). 107…”
Section: Oxymatrinementioning
confidence: 99%
“…106 In addition, three novel compounds (YF3-5, YF3-7 and YF3-9) all demonstrated anti-proliferation activity, of which YF3-5 showed the strongest anti-proliferation properties against the four human cancer cell lines (BT20 breast, MCF-7 breast, A549 lung and U2OS osteosarcoma cells). 107…”
Section: Oxymatrinementioning
confidence: 99%
“…Recent studies showed that matrine inhibited cell growth, induced apoptosis, and reversed multidrug resistance through inhibiting PI3K/AKT pathway when it was used alone or in combination with other anticancer agents in human breast, prostate, and bladder cancer cells (Liao et al, 2017; Li Q. et al, 2018a; Zhou et al, 2018). The structure analysis revealed that matrine contains a variety of components in which the carbon–carbon double bond at 14′ of its skeleton is critical for anticancer activity (Jiang et al, 2017). Studies have shown that MASM (6aS, 10S, 11aR, 11bR, 11cS)-10-methylamino-dodecahydro-3a,7a-diazabenzo (de), a novel derivative of matrine, markedly inhibited cell growth and induced apoptosis against human liver cancer Hep3B and Huh-7 cells in vitro and significantly suppressed the tumor growth of Huh-7 xenograft in vivo through inhibiting the PI3K/AKT/mTOR pathway (Liu Y. et al, 2017).…”
Section: Anticancer Tcms Through Targeting Pi3k/akt/mtor Pathwaymentioning
confidence: 99%
“…Matrine ( MA ), a quinolizidine alkaloid and an important natural product, is isolated from the plant species of the family Fabaceae, Sophora flavescens Aiton, Sophora tonkinensis Gagnep, Sophora alopecuroides L. [ 1 , 2 , 3 ]. MA and its analogs possess a variety of biological properties, such as anticancer activity, anti-inflammatory activity, insecticidal activity, antimicrobial activity, and antiviral activity; MA alkaloids are excellent precursors for structural modification and thus have attracted great interest from scholars [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. As an insecticide, MA has remarkable insecticidal activity against a variety of agricultural pests, such as Bradysia odoriphaga Yang et Zhang, Cnaphalocroci smedinalis (Guenee, 1854), Ectropis obliqua hypulina Wehrli, Clostera anachoreta Denis and Schiffermüller,1775, Eriosoma lanigerum (Hausmann), Psylla chinensis Yang et Li, Mesonura rufonota Rohwer, and Aceri macrodonis Keifer, with contact toxicity and gastric toxicity as the main modes of action [ 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%